Forage yield and sward structure characteristics of Brachiaria brizantha cultivars under grazing - Euclides, Valéria Pacheco Batista; Macedo, Manuel Cláudio Motta; Valle, Cacilda Borges do; Barbosa, Rodrigo Amorim; Gonçalves, Welhington Velasques (Pesquisa Agropecuaria Brasileira, 2009)
The objective of this work was to evaluate the animal grazing effect on forage yield and on the pasture structural characteristics of cultivars Marandu, Xaraés and Piatã of Brachiaria brizantha. The experimental design was a randomized complete block, with three treatments and two replicates. The paddocks (2 ha) were divided into two, and submitted to alternated grazing, with 28 days of grazing and 28 days of rest. Evaluations were made with three tester steers per paddock, and additional steers were added and removed from each paddock, to ensure post-grazing residues of about 3 Mg ha-1 dry matter. All pastures were sampled, before and after grazing, in order to estimate forage mass and percentages of the morphological components. The pre-grazing forage mass for 'Xaraés' pasture was greater than for 'Marandu'. 'Piatã' had pre-grazing forage mass similar to the others. The main differences in the sward structures between cultivars were stem accumulation and, consequently, the reduction in the leaf blade:stem ratio, in 'Piatã' during the rainy season and in 'Xaraés' during the dry season, which suggests different grazing management for these cultivars. Similarly to 'Marandu', Piatã and Xaraés cultivars are well adapted to Cerrado soils, and are new alternatives for forage diversification.
Keywords: leaf lamina accumulation; maintenance fertilization; palisade grass; Cerrado; morphological component; flowering time